Answer:
5
Step-by-step explanation:
its 5
D 2520 -------------------------------------------
Answer: 5(x-1)
Step-by-step explanation:
5*x = 5x
5*-1 = -5
therefore the answer is 5(x-1)
(2c) / (3b)
(2*6) / (3*2) =
12/6 =
2 <===
12√18-6√20-3√50-8√45
<em>*Break each radical up into the product of a radical of a perfect square and a second radical*</em>
12(√9*√2)-6(√4*√5)-3(√25*√2)-8(√9*√5)
<em>*Simplify the radicals*</em>
12(3√2)-6(2√5)-3(5√2)-8(3√5)
<em>*Distribute*</em>
36√2-12√5-15√2-24√5
<em>*Combine like terms</em>*
21√2-36√5
Hope this helps!!